Efikasi Insektisida Nabati terhadap Mortalitas Ulat Grayak (Spodoptera Litura) pada Tanaman Sawi (Brassica Juncea L.) - Rio Saputra Silaban; Azwana Azwana; Asmah Indrawati (Journal of Natural Sciences, 2022)
The aim of the study was to examine the effectiveness of various extracts of vegetable insecticides in controlling armyworm (Spodoptera litura) on mustard plants. The study was carried out in Sampali Village, Percut Sei Tuan District, North Sumatra, from May to June 2019. Effectiveness of Vegetable Insecticides on Death Rate Grayak caterpillars, plant height (cm) and mustard production per plot (g). The results showed that the application of botanical insecticides had a very significant effect on observations 17, 19 and 21 day after planting on the mortality of armyworms, as well as the intensity of damage to the mustard plant. Effectiveness of Vegetable Insecticides (%) on the Death Speed of Grayak Caterpillars where 50% tuba root had the highest effectiveness. (63,30) and the production of mustard greens also showed a very significant difference. It can be seen that the use of tuba root as a vegetable insecticide is quite effective in controlling armyworm (Spodoptera litura) on mustard plants.